Vandetanib (Zactima, ZD6474) Antagonizes ABCC1- and ABCG2-Mediated Multidrug Resistance by Inhibition of Their Transport Function - Zheng, Li-sheng; Wang, Fang; Li, Yu-hong; Zhang, Xu; Chen, Li-ming; Liang, Yong-ju; Dai, Chun-ling; Yan, Yan-yan; Tao, Li-yang; Mi, Yan-jun; Yang, An-kui; To, Kenneth Kin Wah; et al. (PLOS ONE, 2009)
Background ABCC1 and ABCG2 are ubiquitous ATP-binding cassette transmembrane proteins that play an important role in multidrug resistance (MDR). In this study, we evaluated the possible interaction of vandetanib, an orally administered drug inhibiting multiple receptor tyrosine kinases, with ABCC1 and ABCG2 in vitro. Methodology and Principal Findings MDR cancer cells overexpressing ABCC1 or ABCG2 and their sensitive parental cell lines were used. MTT assay showed that vandetanib had moderate and almost equal-potent anti-proliferative activity in both sensitive parental and MDR cancer cells. Concomitant treatment of MDR cells with vandetanib and specific inhibitors of ABCC1 or ABCG2 did not alter their sensitivity to the former drug. On the other hand, clinically attainable but non-toxic doses of vandetanib were found to significantly enhance the sensitivity of MDR cancer cells to ABCC1 or ABCG2 substrate antitumor drugs. Flow cytometric analysis showed that vandetanib treatment significantly increase the intracellular accumulation of doxorubicin and rhodamine 123, substrates of ABCC1 and ABCG2 respectively, in a dose-dependent manner (P<0.05). However, no significant effect was shown in sensitive parental cell lines. Reverse transcription-PCR and Western blot analysis showed that vandetanib did not change the expression of ABCC1 and ABCG2 at both mRNA and protein levels. Furthermore, total and phosphorylated forms of AKT and ERK1/2 remained unchanged after vandetanib treatment in both sensitive and MDR cancer cells. Conclusions Vandetanib is unlikely to be a substrate of ABCC1 or ABCG2. It overcomes ABCC1- and ABCG2-mediated drug resistance by inhibiting the transporter activity, independent of the blockade of AKT and ERK1/2 signal transduction pathways.